Verifier-based password-authenticated key exchange protocol for three-party - LI Wen-min; WEN Qiao-yan; ZHANG Hua (Tongxin xuebao)
The fundamental security goal of verifier-based password-authenticated key exchange protocol is security against dictionary attack and server compromise attack.An efficient verifier-based protocol for three parties was pro-posed which contains the following characteristics: against dictionary attack and server compromise attack;providing key secrecy and forward secrecy;ensuring no key control;against known-key attack and man in-the-middle attack and re-ceiving four session keys in performing protocol one time.